Commerce Ethics of Muhammad PBUH’ and Universal Values in Era of Prophet Hood - Andi Suwandi (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
Muhammad PBUH, primarily business along with his father since as early as his childhood. Whilst he grown up, he commenced to setup his own venture and also have a joint venture with Siti Khadijah based on mudharabah scheme. He is gifted with great wisdom in trading and has allowed him gaining great benefit through it. Due to his moral in trading, it leads to his marriage with Siti Khadijah. Unquestionably there were features on the ethics and morals in the trade that Muhammad PBUH has represented. A matter of concern was his morality that shown during trade leads to his marriage with Siti Khadijah who was initially his business colleague previously and what was the commercial strategy that empowers him to a vast profit during trading. Thus, this study endeavor to define and detail the ethics and morals in trading that has been shown by Muhammad PBUH prior his prophet hood. The results of this study display the conflicting fact in practices that has been applied amongst the community back at that time. His is abundant in honest, fairness, friendly and compassionate to the buyer, and never set up a high price, and also detail in transaction record consequential him loved by many people. Alongside the combination of his aptitude in negotiation and intelligence, he was proficient to “read” the market opportunities and learning cultural and geographical conditions of each target market led him to higher profits than other merchants. In addition, this study also articulated sixteen Muhammad PBUH’ universal values in commerce  such; honest, trustworthy, fair, polite and affectionate in trade, buy-sell applies only based on mutual consent, not involved in usurious practices', only legitimate and permitted item that will sell, avoid argument with partners and buyers, no oath in the name of idols, hoarding the goodies (ikhtisar) is not allowed, damaged item’ replacement policy, avoid competition on price, small profits is acceptable, pay his employee as soon as the job is done, always record transaction, and be generous. Those ethics and values actually resemble to such practice by Islamic merchants to highlight Islamic values in commerce nowadays. Keyword: Trading Business Ethics, Muhammad PBUH, prior to prophet hood.